DIAGNOSTIC VALUE OF SPUTUM AND ENDOTRACHEAL ASPIRATE GRAM STAIN - Viktorija Tomič (Zdravniški Vestnik, 2002)
Background. For decades the microscopic examination of sample Gram stain has been one of the basic diagnostic procedures in the microbiology laboratory. Still opinions about usefulness of sputum and endotracheal aspirate Gram stains in initial management of patients with lower respiratory tract infections differ. We were interested in the value of sputum and endotracheal aspirate Gram stain in a nonselected group of patients. Material and methods. During 7 months period we examined 1739 sputum samples and 88 endotracheal aspirates. The samples were evaluated for quality by determining the amount of squamous cells and leukocytes. We compared the Gram stain examination to culture results. Results. Due to poor quality we rejected 48% of sputum samples. The sensitivity of Gram stain for Streptococcus pneumoniae, Haemophilus sp. and Moraxella catarrhalis was 61%, 74% and 73%, respectively. Predominance of one typical bacterial morphotype (eg. Gram positive lancet-shaped diplococci) correlated perfectly with culture. Conclusions. Examination of sputum and endotracheal aspirate Gram stain is useful procedure in patient management and in bacteriological culture evaluation.